2008
DOI: 10.1080/00207450701769364
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative Immunohistochemical Analysis of Nitric Oxide Synthases and Apoptosis Regulator Proteins in the Fetal Rat Brain Following Maternal Uterine Artery Ligation

Abstract: The purpose of this study was to determine the relation between nitric oxide synthases (calcium-independent iNOS and calcium-dependent eNOS) and apoptosis regulator proteins (anti-apoptotic Bcl-2, pro-apoptotic p53) of fetal rat brain in experimental intrauterine growth retardation (IUGR) model via quantitative immunohistochemistry. Cortical zone of parietal cerebral cortex and ventricular zone of third ventricle were studied following bilateral uterine artery ligation on gestational day 18. Significant increa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
12
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(13 citation statements)
references
References 30 publications
0
12
1
Order By: Relevance
“…Several studies reported that apoptosis mediated by iNOS activation could be accompanied by eNOS depression [28] or activation [31]. On the contrary, we found that eNOS protein expression was unchanged 2 h after IH exposure.…”
Section: Discussioncontrasting
confidence: 54%
“…Several studies reported that apoptosis mediated by iNOS activation could be accompanied by eNOS depression [28] or activation [31]. On the contrary, we found that eNOS protein expression was unchanged 2 h after IH exposure.…”
Section: Discussioncontrasting
confidence: 54%
“…Bcl‐2 is an important anti‐apoptotic protein, while p53 is an pro‐apoptotic protein (Table ) . Studies of rats with placental insufficiency at birth demonstrated reduced Bcl‐2 expression in the ventricular zone and reduced Bcl‐2 mRNA levels . However, p53 (mRNA and protein) and activated phospho‐p53 were upregulated within the cortical zone, CA1 region, subcortical and periventricular white matter, and the amygdala .…”
Section: Resultsmentioning
confidence: 99%
“…Studies of rats with placental insufficiency at birth demonstrated reduced Bcl‐2 expression in the ventricular zone and reduced Bcl‐2 mRNA levels . However, p53 (mRNA and protein) and activated phospho‐p53 were upregulated within the cortical zone, CA1 region, subcortical and periventricular white matter, and the amygdala . Under physiological conditions, p53 should result in murine double minute 2 transcription, which functions to attenuate the apoptotic effect of p53 .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations